2012
DOI: 10.1134/s1070428012050028
|View full text |Cite
|
Sign up to set email alerts
|

New approach to the synthesis of 1,3-dioxolanes

Abstract: Application of ethanol to the synthesis of 1,3-dioxolanes by the condensation of carbonyl compounds with vicinal diols results in a high yield of the reaction product and considerably reduces the duration of the process. It is assumed that the effect of the ethanol is caused by the adduct formation with carbonyl compounds (hemiacetals) which behave as active intermediates of the condensation. A cyclic ketal of acetone with glycerol obtained with the help of ethanol was used as a basis component in the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The glycerol acetalization reaction mechanism in the presence of an acid catalyst that leads to the formation of both five- and six-membered rings (ketals) is illustrated in Figure 11 (Voleva et al, 2012 ). Nanda et al ( 2014a ) have also reported a two-step processes for glycerol acetalization reaction.…”
Section: Impacts Of Various Reaction Parameters On Catalytic Performamentioning
confidence: 99%
“…The glycerol acetalization reaction mechanism in the presence of an acid catalyst that leads to the formation of both five- and six-membered rings (ketals) is illustrated in Figure 11 (Voleva et al, 2012 ). Nanda et al ( 2014a ) have also reported a two-step processes for glycerol acetalization reaction.…”
Section: Impacts Of Various Reaction Parameters On Catalytic Performamentioning
confidence: 99%
“…Finally, the synthesis of glycerol ketals using ketones with longer alkyl chains, 124,126 or with the remaining hydroxyl group protected by etherification 118 or esterification reactions 124,127 has also been described. The interest of these derivatives is the possibility of tuning the polarity of the product, which should be interesting from the point of view of their utility as solvents.…”
Section: Glycerol Acetals and Ketalsmentioning
confidence: 99%
“…The method was especially effective in the case of high‐boiling carbonyl compounds, whereas with cyclopentanone further yield increase was hindered by undesirable cyclopentanone leaching (bp=130‐131 °C) with the argon flow. However, based on some literature data it can be supposed, that successful acetone stripping in this case could be performed by use of a Vigreux column …”
Section: Resultsmentioning
confidence: 96%